The Effect of Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence on Ethical Behavior of Educator Accountants at Private Universities in North Sumatra - Fitriani Saragih; Novien Rialdy; Edisah Putra Nainggolan (AIBPM Publisher, 2021)
Ethical behavior is defined as behavior that adheres to universally accepted societal norms in regards to right and good activities. This ethical behavior can influence the quality of individuals (workers) who are influenced by external variables that create principles that are lived in the shape of behavior. The purpose of this study was to determine the effect of intellectual intelligence, emotional intelligence and spiritual intelligence on the ethical behavior of educator accountants at private universities in North Sumatra. The population in this study were all accounting lecturers who teach at private universities in North Sumatra. While the number of samples in the study was a sample of 206 educator accountants. Questionnaires and interviews are used to collect data, and multiple linear regression is used to analyze it. The findings revealed that intellectual intelligence, emotional intelligence, and spiritual intelligence all had a partial and simultaneous impact on the ethical behavior of educator accountants at private colleges in North Sumatra.